Evidence of low vitamin D intakes in the Australian population points to a need for data‐driven nutrition policy for improving population vitamin D status. Issue 1 (25th March 2022) - Dunlop, Eleanor; Boorman, Julie L.; Hambridge, Tracy L.; McNeill, Jessica; James, Anthony P.; Kiely, Mairead; Nowson, Caryl A.; Rangan, Anna; Cunningham, Judy; Adorno, Paul; Atyeo, Paul; Black, Lucinda J.
Abstract: Background: Nearly one in four Australian adults is vitamin D deficient (serum 25‐hydroxyvitamin D concentrations [25(OH)D] < 50 nmol L –1 ) and current vitamin D intakes in the Australian population are unknown. Internationally, vitamin D intakes are commonly below recommendations, although estimates generally rely on food composition data that do not include 25(OH)D. We aimed to estimate usual vitamin D intakes in the Australian population. Methods: Nationally representative food consumption data were collected for Australians aged ≥ 2 years ( n = 12, 153) as part of the cross‐sectional 2011–2013 Australian Health Survey (AHS). New analytical vitamin D food composition data for vitamin D3, 25(OH)D3, vitamin D2 and 25(OH)D2 were mapped to foods and beverages that were commonly consumed by AHS participants. Usual vitamin D intakes (µg day –1 ) by sex and age group were estimated using the National Cancer Institute method. Results: Assuming a 25(OH)D bioactivity factor of 1, mean daily intakes of vitamin D ranged between 1.84 and 3.25 µg day –1 . Compared to the estimated average requirement of 10 µg day –1 recommended by the Institute of Medicine, more than 95% of people had inadequate vitamin D intakes. We estimated that no participant exceeded the Institute of Medicine's Upper Level of Intake (63–100 µg day –1, depending on age group). Conclusions: Usual vitamin D intakes in Australia are low. This evidence, paired with the high prevalence of vitamin D deficiency in Australia, suggests that data‐driven nutrition policy is required to safely increase dietary intakes of vitamin D and improve vitamin D status at the population level. Key points: We quantified usual intakes of vitamin D in the Australian population using up‐to‐date, comprehensive vitamin D composition data and nationally representative food consumption data. Mean usual intakes ranged between 1.8 and 3.2 µg day –1, assuming equal bioactivity of the D vitamers. We estimated that more than 95% of the population had inadequate vitamin D intakes compared to the estimated average requirement (10 µg day –1 ) recommended by the Institute of Medicine. This new evidence of low vitamin D intakes, together with high prevalence of vitamin D deficiency in Australia, suggests that data driven nutrition policy is required to safely increase intakes of vitamin D and improve vitamin D status at the population level. Abstract : Vitamin D intakes are low in Australia.